Adaptation Strategy for Home-Based Batik Enterprise Space in Arab Village Sugihwaras Pekalongan - Mohammad Sahid Indraswara; Atiek Suprapti; Agung Budi Sardjono; Suci Senjana; Septana Bagus Pribadi (Journal of Islamic Architecture, 2023)
Changes in the pattern of batik trade in Sugihwaras Arab Village encourage the community to adapt by utilising the space in their homes to become Home Based Enterprises (HBEs) of batik space. HBEs batik space is a characteristic of Sugihwaras Arab Village as a batik trading area. The people of Arab Village have adapted by implementing the "hijab concept" to maintain privacy between domestic activities and the batik business. The application of the "hijab concept" is something unique to study because the "hijab concept" is usually only applied to Muslim women's clothing. Based on this phenomenon, researchers are interested in examining how Hijab is used as an adaptation strategy in a batik Home Based Enterprises space. This study examines the "hijab concept" as an adaptation strategy in the batik business space. The research method uses qualitative-descriptive so that researchers can describe phenomena and information on objects in detail. This research aims to find the implementation of the "hijab concept" as a space adaptation strategy to separate the domestic space and the Home-Based Enterprises. The importance of the study is a cause of the increasing role of women in running a household-based business, so an adaptation strategy is needed by separating the domestic space and the business space. The novelty of this study is the formation of layers of "hijab" in the Batik Home-Based Enterprises space in Arab Village Sugihwaras Pekalongan.